Ectodomain shedding of Fcα receptor is mediated by ADAM10 and ADAM17 - Peng, Min (Blackwell Science Inc, 2010)
FcαR (CD89) plays important roles in immunoglobulin A (IgA)-mediated immune responses. Soluble forms of FcαR (sFcαR) are found in the culture supernatants of FcαR-expressing cells, in human serum and in the serum of FcαR transgenic mice, and have been suggested to be produced through a proteolytic process. However, little is known about the mechanism involved in the proteolytic release of sFcαR. In this study, we investigated the shedding mechanism of FcαR and determined the nature of the proteinase involved in FcαR shedding. In chemical inhibitor assays, shedding of FcαR was dramatically inhibited by EDTA, EGTA and a broad-spectrum metalloproteinase inhibitor, GM6001, suggesting that a metalloproteinase was responsible for FcαR shedding. Overexpression of dominant-negative mutants of ADAM (a disintegrin and metalloproteinase) 10 and ADAM17 markedly inhibited the production of sFcαR. Finally, knockdown of both endogenous ADAM10 and endogenous ADAM17 inhibited FcαR shedding, demonstrating that ADAM10 and ADAM17 were involved in the shedding of FcαR. The characterization of ADAM10 and ADAM17 as sFcαR-releasing enzymes provides a novel insight into the molecular mechanism of sFcαR production and will help in further elucidation of the physiological and pathological roles of sFcαR.